Recompression after percutaneous transforaminal endoscopic decompression for degenerative lumbar spinal stenosis: risk factors and outcomes of two different reoperation procedures - Yuan, Shuo; Wang, Aobo; Fan, Ning; Du, Peng; Wang, Tianyi; Li, Jian; Zhu, Wenyi; Zang, Lei (Frontiers in Surgery, 2024)
Purpose To determine the risk factors for recompression after percutaneous transforaminal endoscopic decompression (PTED) for the treatment of degenerative lumbar spinal stenosis (DLSS) and compare the outcomes of PTED and posterior lumbar interbody fusion (PLIF) as revision surgery. Methods We retrospectively evaluated 820 consecutive DLSS patients who underwent PTED at our institution. 26 patients developed postoperative recompression and underwent reoperation. In total, 208 patients with satisfactory clinical outcomes were enrolled in the control group. The demographic and imaging data of each patient were recorded. Univariate and multivariate analyses were performed to assess risk factors for recompression. Additionally, patients with recompression were divided into PTED and PLIF groups according to the reoperation procedure. The clinical outcomes of the two groups were compared using independent-sample t-tests. Results The grade of surgical-level disc degeneration [odds ratio (OR): 2.551, p = 0.045] and the number of disc degeneration levels (OR: 11.985, p < 0.001) were independent risk factors for recompression after PTED. There was no significant difference in the visual analog score (VAS) and Oswestry disability index (ODI) two weeks postoperatively between the PTED and PLIF groups for surgical treatment. However, the mean VAS of back pain (14.1 vs. 20.5, p = 0.016) and ODI (16.0 vs. 21.8, p = 0.016) of patients in the PLIF group were smaller than those in the PTED group at the final follow-up. Conclusion More severe degeneration and degenerated levels indicate a higher recompression rate after PTED. Although both PTED and PLIF could achieve immediate relief postoperatively in the treatment of recompression, the final follow-up results showed that the outcome of PLIF appeared better than that of PTED.